Standardization of the Spot-on-the-Lawn antagonism test in the inhibition of Salmonella Heidelberg by Lactobacillus salivarius - Ribeiro, G. C. [UNESP] (2024)
Using extremes concentrations for both bacteria involved in the Spot -on -the -Lawn antagonism test is highly contraindicated, as results may vary mor than expected and thus, not be reliable. The present study recommends a standardization model with similar values for the concentration of both bacteria to avoid high variability, and non-replicability as well as to ensure reliable results. Using a nephelometric scale such as McFarland (0.5 tube; 1.5 x 108 CFU/mL) is highly advised, which is a turbidity standard pattern used to pre -assess the bacterial concentration in liquid culture media. It is also advised to perform bacterial quantification through serial decimal counts, ensuring similar concentrations of both probiotic and pathogen bacteria.